Inhibition of Bmp signaling affects growth and differentiation in the anagen hair follicle - Kulessa, Holger (Oxford University Press, 2000)
Growth and differentiation of postnatal hair follicles are controlled by reciprocal interactions between the dermal papilla and the surrounding epidermal hair precursors. The molecular nature of these interactions is largely unknown, but they are likely to involve several families of signaling molecules, including Fgfs, Wnts and Bmps. To analyze the function of Bmp signaling in postnatal hair development, we have generated transgenic mice expressing the Bmp inhibitor, Noggin, under the control of the proximal Msx2 promoter, which drives expression in proliferating hair matrix cells and differentiating hair precursor cells. Differentiation of the hair shaft but not the inner root sheath is severely impaired in Msx2–Noggin transgenic mice. In addition to hair keratins, the expression of several transcription factors implicated in hair development, including Foxn1 and Hoxc13, is severely reduced in the transgenic hair follicles. Proliferating cells, which are normally restricted to the hair matrix surrounding the dermal papilla, are found in the precortex and hair shaft region. These results identify Bmps as key regulators of the genetic program controlling hair shaft differentiation in postnatal hair follicles.